Effective English Learning and Character Education for Young Learners through Animated Video of Indonesian Folklore - Silvia Ade Yusfika (Publikasi Indonesia, 2021)
The objective of this study is to determine the effectiveness of learning English for junior high school students on local Indonesian literature in English, listening and understanding the content of English language skills based on the popular Indonesian folktale